(untitled) (International Seven Journal of Multidisciplinary, 2024)
The New Information and Communication Technologies are tools that can help in everyday life, as well as offering support to contribute in the classroom with the aim of instrumentalizing the teaching of geography. This paper presents a report on a classroom experience with children aged six (6) and seven (7) in which the Google Earth application is used to demonstrate how children in the literacy phase express and use geographical knowledge in a meaningful and spontaneous way in their daily lives. However, there are criticisms of the risks of romanticizing the use of information and communication technologies. That said, the step-by-step process is described, from arriving at the school to using the app, the frustration at not being able to use it in the first lesson, and the difficulty of accessing the necessary resources. The children’s speeches are transcribed, their reactions as they follow and view the images that the Google Earth application makes available, during the lesson proposed and carried out. At the end, we present some images that reveal how the children express their spatial experiences in drawings. Thus, we advocate the possibility and importance that from elementary school onwards, including in literacy classes for children aged six (6) and seven (7), it is conceivable to develop activities that contribute to the construction of ideas and knowledge pertaining to the teaching of school geography with children who are at the beginning of the literacy process of their language.